The geometry of the accessible sets of vector fields / A.Y. Narmanov and I. Ganiev - Narmanov, A.Y; Ganiev, I. (2015)
In this paper it is studied geometry of accessible sets of family of vector fields. It is proved that sets of 0- accessible sets are smooth submanifolds of an orbit. It is also proved that on the any manifold there is a system of vector fields consisting of three vector fields, such that each set of 0- accessible sets coincide with the manifold.